Modification and validation of the COVID-19 stigma instrument in nurses: A cross-sectional survey - Huang, Feifei; Sun, Wenxiu; Li, Yonglin; Zhang, Lin; Chen, Wei-Ti (Frontiers in Psychology, 2023)
Background: Nurses taking care of patients with infectious diseases have suffered from noticeable societal stigma, however currently, there is no validated scale to measure such stigma. This study aimed to revise and validate the COVID-19 Stigma Instrument-Nurse -Version 3 (CSI-N-3) by using item response theory (IRT) as well as classical test theory analysis. Methods: In phase I, the Chinese CSI-N-3 was modified from the English version of HIV/AIDS Stigma Instrument–Nurse based on standard cross-cultural procedures, including modifications, translation/back translations, pilot testing, and psychometric testing with classical test theory and Rasch analysis. In phase II, a cross-sectional study using cluster sampling was conducted among 249 eligible nurses who worked in a COVID-19-designed hospital in Shanghai, China. The influencing factors of COVID-19–associated stigma were analyzed through regression analysis. Results: In phase I, the two-factor structure was verified by confirmatory factor analysis, which indicated a good model fit. The 15-item CSI-N-3 achieved Cronbach's α of 0.71 to 0.84, and composite reliability of 0.83 to 0.91. The concurrent validity was established by significant association with self-reported physical, psychological, and social support levels (r=-0.18, -0.20, &-0.21, p < 0.01). In IRT analysis, the CSI-N-3 has ordered response thresholds, with the Item Reliability and Separation Index of 0.95 and 4.15, respectively, and the Person Reliability and Separation Index of 0.20 and 0.50, respectively. The infit and outfit mean squares for each item ranged from 0.39 to 1.57. In phase II, the mean score for the CSI-N-3 in Chinese nurses was 2.80 ± 3.73. Regression analysis showed that social support was the only factor affecting nurses' COVID-19–associated stigma (standardized coefficients β= -0.21, 95% confidence interval: -0.73~-0.19). Conclusions: The instrument CSI-N-3 is equipped with rigorous psychometric properties that can be used to measure COVID-19–associated stigma during and after the COVID-19 pandemic among nurses. The use of this instrument may facilitate the evaluation of tailored stigma-reduction interventions.